Integration of Green Islam and Agro-Ecology for Food Sovereignty - Millah, Ahamad Sihabul; Suharko, Suharko; Ikhwan, Hakimul (Universitas Negeri Semarang, 2020)
This paper discuses integration between Green Islam and an agro-ecological movement in establishing food sovereignty practiced by a community of Pesantren Ath-Thariq Garut, West Java. They have struggled for food sovereignty through agricultural production models by prioritizing local wisdom, respecting to organisms, dividing land with zoning systems, planting with polyculture system, consuming diversified food, and self-mastering to make fertilizer. Furthermore, they also have preserved local and inherited seeds as an approach to cultivate their farming.